Design, synthesis, and antiproliferative effect of 2, 9‐bis[4‐(pyridinylalkylaminomethyl)phenyl]‐1, 10‐phenanthroline derivatives on human leukemic cells by targeting G‐quadruplex. Issue 8 (14th April 2021) - Guillon, Jean; Denevault‐Sabourin, Caroline; Chevret, Edith; Brachet‐Botineau, Marie; Milano, Vittoria; Guédin‐Beaurepaire, Aurore; Moreau, Stéphane; Ronga, Luisa; Savrimoutou, Solène; Rubio, Sandra; Ferrer, Jacky; Lamarche, Jeremy; et al.
Abstract: Current multiagent chemotherapy regimens have improved the cure rate in acute leukemia patients, but they are highly toxic and poorly efficient in relapsed patients. To improve the treatment approaches, new specific molecules are needed. The G‐quadruplexes (G4s), which are noncanonical nucleic acid structures found in specific guanine‐rich DNA or RNA, are involved in many cellular events, including control of gene expression. G4s are considered as targets for the development of anticancer agents. Heterocyclic molecules are well known to target and stabilize G4 structures. Thus, a new series of 2, 9‐bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthroline derivatives (1a –i ) was designed, synthesized, and evaluated against five human myeloid leukemia cell lines (K562, KU812, MV4‐11, HL60, and U937). Their ability to stabilize various oncogene promoter G4 structures (c‐MYC, BCL‐2, and K‐RAS) as well as the telomeric G4 was also determined through the fluorescence resonance energy transfer melting assay and native mass spectrometry. In addition, the more bioactive ligands 1g –i were tested for telomerase activity in HuT78 and MV4‐11 protein extracts. Abstract : 2, 9‐Bis[(substituted‐aminomethyl)phenyl]‐1, 10‐phenanthrolines 1a –i were designed, synthesized, and evaluated against five human myeloid leukemia cell lines. Their ability to stabilize the c‐MYC, BCL‐2, and K‐RAS oncogene promoter G4 structures was determined by fluorescence resonance energy transfer melting assay and native mass spectrometry. Telomerase activity in HuT78 and MV4‐11 protein extracts was investigated in the presence of the more bioactive ligands.